Delays in health care seeking for diarrheal disease and associated factors among caregivers of under five children in health centers of northwest Ethiopia: a mixed-method study - Asnakech Marew; Zenebe Jebero Zaza; Shiferaw Birhanu; Amare Belachew; Tsehaynew Kasse (BMC Public Health)
Abstract Background Approximately 70% of child deaths due to diarrhea are caused by a lack of timely healthcare. However, there was little evidence of factors associated with delays in seeking health care for patients with diarrheal diseases in the study area. Therefore, this study aimed to investigate delays in seeking healthcare for children with diarrhea and identify associated factors among caregivers in health centers of Northwest Ethiopia. Method and materials An institution-based mixed study method was conducted from May to June 2022. Quantitative data were collected from 374 participants who were selected by systematic random sampling using a structured interviewer-administered questionnaire and chart review. The data were analyzed using the Statistical Package for Social Science software version 25. Bivariable and multivariable logistic regression models were used to identify associated factors. Variables with a p- value < 0.05 in the multivariable analysis were considered to be significantly associated. Qualitative data were collected from participants in waiting area after receiving treatments via in-depth interviews and analyzed using open-source software. The qualitative data were transcribed, translated, coded, thematized, and interpreted accordingly. Results In this study, 53.48% of patients experienced delays in seeking healthcare for diarrhea. A large family size (adjusted odds ratio (AOR) = 2.64, 95% CI: 1.26–5.4), poor knowledge about diarrhea danger signs (AOR = 3.25, 95% CI: 1.6–6.6), difficulty paying for treatment (AOR = 2.95, 95% CI: 1.6–5.3), not visiting health facilities as the first response to diarrhea (AOR = 3.94, 95% CI: 1.96–7.9), only diarrhea (AOR = 2.39, 95% CI: 1.01–5.63), and no information about early healthcare seeking (AOR = 4.88, 95% CI: 1.91–12.43) were identified; moreover, from the qualitative findings, mothers’ perceptions of the illness were mild, poor service provision, and economic problems were determinants of delay. Awareness, barriers, compliance, and perception emerged as themes. Conclusion The prevalence of delays in seeking healthcare for children with diarrhea was high. This poses a negative health risk to the lives of children and their caregivers. A large family size, poor knowledge about diarrhea danger signs, difficulty paying for treatment, and many others were factors associated with delayed health care seeking. Hence, the government and other concerned stakeholders should give due emphasis to tackling the identified causes of delay in seeking health care for children under five years of age with diarrhea by diverting community focus toward timely care seeking and disease prevention.